Prevalence of established vertebral fragility fractures in patients admitted with acute hip fracture. (2022) - Ghobrial, Hedra; Ali, Asad; Ogunjembula, Ibrahim; Abbas, Hashim; Khalid, Mohammed; Dwivedi, Rajesh
No abstract available